Z shaped like resonator with crystal in the presence of flat mirror based standing wave ratio for optical antenna systems - Iraj Sadegh Amiri; Ahmed Nabih Zaki Rashed; Preecha Yupapin (Institute of Advanced Engineering and Science, 2020)
This study has outlined the Z resonator shaped with Brewster crystal in the presence of flat mirror for measuring the standing wave ratio. Stability parameter and beam radius are simulated versus thickness, refractive index of the crystal and first and second folding ranges. Beam radius variations are studied against phase angle and curvature radius of spherical mirror in T and S planes. Intermode beat frequency of the system is 216.276 MHz and total cavity length is 693.078 mm. It is important the standing wave ratio is dependent on stability parameter and beam radius variations.